Circulating interleukin-38 concentrations in healthy adults - Teufel, Lisa U.; de Graaf, Dennis M.; Netea, Mihai G.; Dinarello, Charles A.; Joosten, Leo A. B.; Arts, Rob J. W. (Frontiers in Immunology, 2022)
Interleukin (IL) 38 is the latest discovered member of the interleukin 1 family, which has anti-inflammatory properties similar to IL-36Ra. Several studies compared circulating IL-38 concentrations in healthy and diseased populations to characterize its role in both auto-immune and inflammatory pathologies, with both higher and lower concentrations being associated with certain diseases. However, in order to use IL-38 as a biomarker, a reference range in healthy adults is needed. To establish a reference IL-38 circulating concentration, accessible data from 25 eligible studies with IL-38 concentrations in healthy adults was collected. To validate the values found in literature, we measured IL-38 concentrations by enzyme-linked immunosorbent assay (ELISA) in several cohorts from our own institute. Additionally, the effect of blood collection techniques, freeze thawing cycles, and hemolysis on IL 38 measurements was assessed. To evaluate the importance of the genetic background of individuals as confounding factor of IL-38 synthesis, we used publicly available eQTL databases with matched data on allele frequencies in individuals of different ethnicities. Mean IL-38 concentrations in the various studies were weighted by their corresponding sample size, resulting in a weighted mean, and weighted upper and lower limits were calculated by mean ± 2 SD. Differences of over 10.000-fold were found in the weighted means between studies, which could not be attributed to the blood collection method or assessment of IL-38 in plasma or serum. Although IL-38 concentrations were markedly higher in Chinese then in European population studies, we could not show an association with the genetic background. From our analysis, a reference range for circulating IL-38 in healthy adults could thus not yet be established.